Facilitating a Whole of University Approach to Aboriginal and Torres Strait Islander Curriculum Development : Leadership Frameworks for Cultural Partnerships : Final Report. - Matthews, Chris (Office for Learning and Teaching, 2016)
The project aimed to develop, implement and evaluate a leadership framework for a culturally appropriate and sustainable whole-of-university approach to Aboriginal and Torres Strait Islander curriculum development, based on a distributive model of leadership. The project set out to: (1) establish multi-level working partnerships and governance structures between local elders and communities, senior management, Indigenous and non-Indigenous academic staff, and students, (2) Develop the capability of cross-cultural institutional project teams to lead curriculum change in disciplinary contexts, (3) recruit and train Indigenous and non-Indigenous teams of faculty curriculum development advisers to facilitate curriculum development at a school/departmental/disciplinary level, (4) pilot and evaluate the leadership-partnership model and best practice resources by faculty curriculum development advisers, and (5) systematically evaluate, review and re-design both the leadership-partnership model and curriculum resources. Within this project, the cultural authority of Aboriginal and Torres Strait Islander peoples is paramount. Hence, notions such as leadership and capacity building need to move beyond the bounds of Western cultural frameworks.